Smallwood Interview 02 - Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. Division of Educational Technology, 1983)
Continuation of Robert Pitt's interview with Joey Smallwood. In this discussion Smallwood talks about a trip to England in his youth and the book collection he sold to finance that trip. He speaks of his regrets in selling a bound book of pamplets from the FABIAN society. He discusses the "great institutions" of the world, such as the Roman Catholic Church, the Masons and the British Parliament. Also discussed is Smallwood's Wesley Collection and his great interest in John Wesley.